Some botanical aspects of Etlingera flexuosa (Zingiberaceae) from Central Sulawesi (Indonesia) and its antifungal activity - Ramadanil Pitopang; Umrah Umrah; Wahyu Harso; Nurainas Nurainas; Muhammad Sulaiman Zubair (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Pitopang R, Umrah, Harso W, Nurainas, Zubair MS. 2020. Some botanical aspects and antifungal activity of Etlingera flexuosa (Zingiberaceae) from Central Sulawesi, Indonesia. Biodiversitas 21: 3547-3553. Etlingera flexuosa is a species of Etlingera endemic to the island of Sulawesi and its natural distribution is restricted to Central and South Sulawesi, where it has been utilized for different purposes. Despite the limited knowledge in the aspects of botany and its antimicrobial activities, the use of plants as a source of alternative solutions to health problems is on the rise. The objectives of this study were to obtain some information about the several botanical aspects of E. flexuosa and its antifungal activity. This research was conducted from March to December 2019 and samples were collected from the montane forest of Lore Lindu National Park (LLNP) near Sedoa Village, Lore Utara Sub-district, Poso District, Indonesia. The identification of plant specimens and extractions was carried out at the Laboratory of Plant Biosystematics, Tadulako University, Palu, Indonesia. The antifungal activity was tested using agar diffusion methods. The results showed that E. flexuosa is a perennial herb naturally distributed in Sulawesi island. It usually grows in the pristine submontane and montane forests, sometimes in light and open condition or on the slope of natural disturbed forest at the altitude of 1500 -1700 m a.s.l. The forest is dominated by Fagaceae family, of which E. flexuosa has been utilized extensively by local community of Topo Baria ethnic for various purposes such as flavor enhancer in food, vegetable, traditional medicine, and as roofing materials. It contains some secondary metabolites such as flavonoids, tannins, saponins, terpenoids, alkaloids and steroids, and also shows antioxidant activity. Conclusively, the extract of E. flexuosa could be used as inhibiting agent for the growth of Candida albicans yeast.